Effect of hydroxyapatite addition into glass ionomer cement on physical, structural and mechanical properties - Wan Jusoh, Wan Nurshamimi (2021)
Glass ionomer cement (GIC) is a well-known restorative material applied in dentistry, especially as restorative and luting materials. The present work aims to enhance the physical, structural and mechanical properties of GIC with the addition of hydroxyapatite (HA) since GIC is lacking in the mechanical strength which then limits the use of GIC as restorative material. In this research, waste materials consisting of clam shell (CS) and soda lime silica (SLS) glass are used in the manufacture of alumino-silicate-fluoride (ASF) glass ceramics through melt-quench technique. Meanwhile, synthesized HA powder was obtained by wet chemical precipitation method using CS as the starting material. The control and modified GIC samples were formulated based on a 3:1:1 ratio referring to ASF glass ceramics/HA: polyacrylic acid (PAA): deionized water. All GIC samples were subjected to four different ageing time before being characterized by density measurement, X-ray diffraction (XRD), Fourier transform infrared (FTIR), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) and compressive strength test. CS and SLS glass are characterized by X-ray fluorescence (XRF) in which the main composition of calcium (Ca) and silicon (Si) respectively encourage the use of waste materials in sample preparation. The existence of fluorapatite (FA) crystal phase in ASF glass ceramics sample was confirmed by XRD, FTIR and FESEM analysis. In addition, the inclusion of HA into the GIC formulation causes an increase in density results. XRD of modified GIC samples detect the presence of fluorohydroxyapatite (FHA) crystal peaks and is confirmed by the OHF chemical bond at FTIR wavenumber ~3550 cm-1. The morphology of FESEM reveals the formation of spherical particles and agglomerated needle-like belonging to apatite crystals. Moreover, ageing time of control and modified GIC samples did not have a significant effect on the structural properties. The calcium to phosphate (Ca/P) ratio of GIC samples in the range of 1.76 to 3.31 allows the suitability of these materials for implantation purposes. Modified GIC samples show higher compressive strength compared to control GIC. The compressive strength increases with increasing ageing time. GIC added with 5 wt.% of commercial HA at 21 days of ageing time produced the highest compressive strength with 90.12 MPa. Overall, the addition of HA into GIC provides excellent results and better properties to encourage its use as a restorative material in dentistry.